Constructing a longitudinal database of targeted regulation of abortion providers laws. (17th June 2019) - Austin, Nichole; Harper, Sam
Abstract: Objective: To build a longitudinal state‐level database on targeted regulation of abortion providers (TRAP) laws. Data Sources: Primary sources included state websites, Lexis Nexis Quicklaw, and WestlawNext. We used a range of secondary sources to pinpoint policy timing. Study Design: This was a state‐level review of TRAP shifts from 1973 to present. Data Collection: We captured data on TRAP policy activity and timing, focusing specifically on ambulatory surgical center (ASC) laws, admitting privilege requirements, and transfer agreements. Principal Findings: Twenty‐five states had ever enacted an ASC, admitting privilege, or transfer agreement law. Many currently face legal challenges. Conclusions: Targeted regulation of abortion providers laws are favored by many states as a way to regulate abortion provision. These data can be used to better understand the impact of these laws.